2015
DOI: 10.5433/1679-0359.2015v36n3p1451
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica: epidemiology, perspectives in the diagnostic and the use of geoprocessing systems for prevalence studies

Abstract: Fasciola hepatica is a parasite that is located in the liver of ruminants with the possibility to infect horses, pigs and humans. The parasite belongs to the Trematoda class, and it is the agent causing the disease called fasciolosis. This disease occurs mainly in temperate regions where climate favors the development of the organism. These conditions must facilitate the development of the intermediate host, the snail of the genus Lymnaea. The infection in domestic animals can lead to decrease in production an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
2
18
0
1
Order By: Relevance
“…Kernel density estimation (6-km scale) (ALEIXO et al, 2015) and point cluster analyses were used to calculate the density and space distribution of infected livers, respectively, using QGIS 3.2.2 software. Linear regression models, using Software R 3.5.1, were used to determine the possible influence of the mean values of abiotic factors (temperature and accumulated precipitation) for each of the four calendar seasons on the number of liver condemnations due to fascioliasis in each respective period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kernel density estimation (6-km scale) (ALEIXO et al, 2015) and point cluster analyses were used to calculate the density and space distribution of infected livers, respectively, using QGIS 3.2.2 software. Linear regression models, using Software R 3.5.1, were used to determine the possible influence of the mean values of abiotic factors (temperature and accumulated precipitation) for each of the four calendar seasons on the number of liver condemnations due to fascioliasis in each respective period.…”
Section: Discussionmentioning
confidence: 99%
“…While epidemiological studies in livestock and humans have been overlooked in many countries, the present work seeks to raise awareness of this important disease, particularly to the large population of buffaloes in Brazil. In cattle, previous studies have also shown that the prevalence of fascioliasis was mainly in the southern states (ALEIXO et al, 2015;DUTRA et al, 2010;SILVA et al, 2016), with an economic loss of approximately US$ 210 million/year (MOLENTO et al, 2018). Bennema et al (2017) have also determined that the best suitability area for F. hepatica development, based on a range of isothermality data was the south region of the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the availability of case reports is of importance for local healthcare providers, particularly when it comes to such a neglected disease. This work is the first human fascioliasis case to be reported in the state of Santa Catarina in the South of Brazil, an area where the occurrence of bovine fascioliasis is well established 7 .…”
Section: Introductionmentioning
confidence: 88%
“…Embora este Estado não seja uma área endêmica para a doença, nos últimos anos com disseminação do hospedeiro intermediário e por consequência de seu parasita, com registro de Lymnaea em Belém (MEDEIROS, 2014). Bennema et al (2014) Fonte: Aleixo et al (2015) De acordo com a figura anterior, para a época descrita, os casos de fasciolose bovina já estão presentes em todas as regiões do Brasil, exceto o Nordeste, com maior incidência para as regiões Sul e Sudeste, onde as condições climáticas são mais favoráveis para o ciclo de vida do parasita.…”
Section: Desenvolvimentounclassified